Idu Tawa Lam Jampi: Mantra-mantra dalam Naskah Surat Incung Kerinci - Hafiful Hadi Sunliensyar (Manuskripta, 2018)
Surat Incung is one of script which used by People of Kerinci in writing old manuscripts both on horn, bark, daluang, bone, and bamboo media. This script is also part of ulu letter which used by several ethnic in southern Sumatera. The results of this research indicate that Surat Incung manuscript contains not only pedigree or ancestral history of a Kerinci group (tembo) and lament prose, but also contain spells. There are about nine copies of the letter containing the known spells to date. The spells in the letter manuscripts include the spell of praise to the spirits of the ancestors, the spell for the protector or personal apparel and the spell for ceremonies or rituals such as for the ritual of rice cultivation. In addition, spells in the letter are influenced by Animism, Hindu-Buddhist and Islam elements. --- Surat Incung merupakan salah satu aksara Indonesia yang digunakan oleh masyarakat Suku Kerinci dalam menulis naskah-naskah kuno baik pada media tanduk, kulit kayu, daluang, tulang, dan bambu. Aksara ini merupakan bagian dari surat ulu yang digunakan oleh beberapa etnis di Sumatera bagian Selatan. Hasil penelitian ini menunjukkan bahwa naskah Surat Incung tidak hanya berisi silsilah atau riwayat nenek moyang suatu kelompok masyarakat Kerinci (tembo) dan prosa ratapan, tetapi juga berisi mantra-mantra. Terdapat sekitar sembilan naskah surat incung berisi mantra-mantra yang diketahui hingga kini. Mantra-mantra dalam naskah Surat Incung berupa mantra pujian terhadap arwah leluhur, mantra untuk pelindung atau pakaian diri serta mantra untuk upacara atau ritual seperti untuk ritual penanaman padi. Selain itu, mantra-mantra dalam Surat Incung dipengaruhi oleh unsur animisme, Hindu-Buddha dan Islam.